Studi Fenomenologi: Pengalaman Interaksi Sosial Lansia Dengan Sesama Lansia Dan Pengasuh Di Panti Sosial Tresna Werdha ‘Sabai Nan Aluih’ Sicincin Kabupaten Padang Pariaman Tahun 2012: Phenomenological Study: Experience of Social Interaction Among Elderly with Fellow Elderly and Caregivers at Tresna Werdha ‘Sabai Nan Aluih’ Social Institution, Sicincin, Padang Pariaman Regency, 2012 - Debby Sinthania; Emil Huriani; Gusti Sumarsih (Fakultas Keperawatan Universitas Andalas, 2012)
Decline in health and physical abilities occurs in the elderly, accompanied by conditions of loneliness and isolation, as seen in the nursing Tresna Werdha, affecting the quantity and quality of older adults' social interactions. This study aimed to explore the experience of social interaction with fellow seniors and caregivers in the Elderly Social Institution Sabai Nan Aluih, Sicincin Pariaman District, 2012. This type of research is a qualitative phenomenological approach. The number of informants was six, selected through purposive sampling with specific criteria, namely the 24-hour caregiver living in the nursing home. Data collection techniques included in-depth interviews, documentation study, and observation. Data collection tools included the interview guide and a tape recorder (recorder). Data processing involved recording, making transcripts, extracts, and thematic analysis of the five variables: cooperation, communication, conflict, caregiver services provided, and actions/caregivers' work methods, both favorable and less favorable. The study found five themes: cooperation in maintaining the cleanliness of the guest house and helping a friend who is ill, elderly efforts to establish communication with peers, causes of conflict among the elderly, types of caregiver services rendered, and the attitude and behavior of caregivers in the interaction. It is suggested that caregivers provide more intensive and proactive social assistance, be more flexible, and actively participate in every nursing activity. It is also recommended that nursing leadership offer training for elderly social workers and further research in quantitative social interaction according to the identified themes.